1958
DOI: 10.1136/bmj.1.5062.76
|View full text |Cite
|
Sign up to set email alerts
|

Masking and Gowning in Nurseries for the Newborn Infant

Abstract: SummaryAn investigation amongst full-time newborn babies in two nurseries has been carried out in an attempt to discover the tsLual routes of spread of Stapli. aur(eius.Initially 53 babies were all found to be nasal carriers by the 10th day, and 11 out of 12 of these babies also carried staphylococci in their stools. Examination of bedding suggested that this was not the immediate source of staphylococci, and prevention of possible contamination from the staff by the use of chlorhexidine handcream or gowns mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1960
1960
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The incidence of sepsis was unaffected: 8 out of 99 infants developed lesions of the skin, compared with 5 out of 100 infants in the previous 11 weeks. These results are in line with those of Forfar and Maccabe (1958), who found that the wearing, by nurses, of gowns individual to each baby made no significant difference to staphylococcal crossinfection.…”
Section: Effect Of Reducing Contact Between Infants and Nursessupporting
confidence: 91%
“…The incidence of sepsis was unaffected: 8 out of 99 infants developed lesions of the skin, compared with 5 out of 100 infants in the previous 11 weeks. These results are in line with those of Forfar and Maccabe (1958), who found that the wearing, by nurses, of gowns individual to each baby made no significant difference to staphylococcal crossinfection.…”
Section: Effect Of Reducing Contact Between Infants and Nursessupporting
confidence: 91%
“…Of 136 colonised infants on ward A, only 29 (21%) 3 matched with phage types isolated from staff working on that ward compared with 104 )6 (68%) of 152 on ward B. The phage types seen in cross infection episodes were not isolated 5 any more often from the attending staff than other phage types.…”
Section: Resultsmentioning
confidence: 90%
“…( The umbilicus has long been recognised as a site of colonisation with Staphylococcus aureus1 whence it can spread from infant to infant causing skin infections and from infant to mother causing breast abscesses.2 The use of hexachlorophane as an umbilical antiseptic treatment prevents colonisation and cross infection,3 4 whereas barrier nursing does not. 5 Doubts about the safety of hexachloro-phane6 7 led to its withdrawal from use with a subsequent increase in staphylococcal infection.8 Chlorhexidine was introduced as an alternative and found to be effective9 and safe. '0 It is now accepted that hexachlorophane, used properly, is also safe"I and it has been reintroduced, though there has been little in the way of comparison between it and chlorhexidene.…”
mentioning
confidence: 99%
“…25-31,37,52-55 Multiple studies have also failed to demonstrate that the routine use of cover gowns decreased bacterial colonization of infants or overall nosocomial infection rates. 29-31 Cover gowns were not well-defined in the articles; however, it is believed that isolation gowns, with or without barrier claims, were used for these studies.…”
Section: Laboratory Studiesmentioning
confidence: 99%